Pelatihan Penulisan Karya Tulis Ilmiah bagi Mahasiswa Program Studi Pendidikan Bahasa Indonesia yang Terkendala Tugas Akhir - Teuku Alamsyah; Rostia Taib; Muhammad Iqbal; Maya Safhida; Nurrahmah Nurrahmah; Dessi Chairani Tanjung (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
The objective of this community service program, implemented in the form of scientific writing training, is to equip students who face challenges in academic writing (theses) with knowledge regarding paragraphs, sentences, spelling, and citation formatting. The participants in this program were 12 students from the English Education Program (PBI), Faculty of Teacher Training and Education (FKIP), USK, who were experiencing difficulties in writing their theses as a form of scientific writing. The activities were conducted in a sequence consisting of a pre-test, presentation of material by the resource persons/community service team, and a post-test. Data collection was carried out using observation, interviews, and tests. The results of the study indicate that (1) all participants were actively and interactively engaged in each session of material presentation, (2) pretest scores related to scientific writing fell into the low category, and (3) posttest scores showed a significant improvement compared to the pretest scores. These findings demonstrate that the training conducted within the context of this community service program provided meaningful benefits to the students who participated as trainees.